INJURY TYPES AND RATES IN AN INTERNATIONAL CRICKET TEAM: APPLICATION OF SUBSEQUENT INJURY CATEGORISATION. Issue 7 (11th March 2014) - Mount, S; Moore, I; Ranson, C
Abstract : Background: Longitudinal injury surveillance may provide valuable information regarding relationships between initial and any subsequent injuries. The Subsequent Injury Categorisation (SIC) (Finch & Cook, 2013) has been proposed as a method for examining these relationships. Objective: To identify priority injury problems and potential risk factors for injury and subsequent injury in international cricket. Design: Prospective injury surveillance using consensus methods and SIC. Setting: International cricket. Participants: All players from one national team squad during over 2 years (2011–2013). Risk factor assessment: The contrasting; injury types, rates and severity, according to body area, position and activity (training or match) at time of injury, and SIC. Main outcome measurement: Training and match injury incidence (per 100 days), prevalence (% of players unavailable) and average days-lost per injury were calculated for each variable along with the percentage of injuries within each SIC. Further analysis of the SIC is in process. Results: 225 injuries were sustained (73 time-loss and 152 non time-loss), with an overall incidence of 10/100 days (7/100 days matches, 3/100 days training), prevalence of 13% and average of 32 days-lost per injury. Ankle, knee and hand regions had the highest incidence, but lumbar and abdomen regions had the greatest days-lost per injury. Fast bowlers had the highest incidence (6/100 days) and prevalence (8%). Wicket-keepers had the greatest days-lost per injury (68 days). Thirty-five percent of the 219 subsequent injuries sustained were coded as being related to a previous injury. Twelve percent of all subsequent injuries were a recurrence. Conclusions: International cricketers have a high rate of non time-loss injury, particularly to the ankle, knee and shoulder whereas thigh strains and lower back injuries result in the greatest time-loss. Injury prevention strategies should target these problems, particularly in fast bowlers. Analysis of the SIC may provide further insight into injury risk predicators.